Human friendly mechatronics : selected papers of the International Conference on Machine Automation : ICMA 2000 : September 27-29, 2000, Osaka, Japan - Arai, Eiji; Arai, Tatsuo; Takano, Masaharu (Elsevier, 2001)
The book includes 61 selected papers from 106 presented at the second International Conference on Machine Automation (ICMA2000). The conference focused, for the first time, on human friendly mechantronics which covers machine systems interacting with human beings, psychological, physiological, and physical behaviors of the human being itself, robotics, human-mimetic mechanical systems, commercial application examples and so on. Machine automation has owed a lot to mechatronics technology in the last decades, however, a paradigm shift is desired and emphasized in the 21st century in every aspect of our society, and mechantronics is not an exception. The paradigm shift in mechatronics is a pursuit of productivity and efficiency to the preference of humans, and it is time that a new concept of a human friendly robot must be proposed that is welcome by human users. The book aims to offer the most up-to-date and valuable information on: & bull;Human Interface & Communication & bull;Human Support Technology & bull;Actuator & Control & bull;Vision & Sensing & bull;Robotics and Design & bull;Manufacturing System We believe this book will bring advanced knowledge and valuable information to the industries as well as to academics and will contribute to the further development in mechatronics and its related fields.